2017
DOI: 10.5152/tud.2017.58997
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with postoperative pain after retrograde intrarenal surgery for kidney stones

Abstract: Objective: We aimed to investigate factors related to early postoperative pain after retrograde intrarenal surgery (RIRS). Material and methods:A prospective data analysis of 250 patients who underwent RIRS due to kidney stones was performed. Postoperative pain was evaluated in all patients by using visual analogue scale (VAS). Patients with severe pain (VAS score ≥7) were separated and included in Group I (n=46). While patients without pain or with insignificant pain were included in Group II (n=204). The imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…Interestingly, a prospective study which included 250 patients undergoing ureteroscopy for stone treatment, demonstrated that the only intraoperative factor which significantly affected immediate post-operative pain was the duration of use of UAS [ 22 ].…”
Section: Complications Associated With Uas Placementmentioning
confidence: 99%
“…Interestingly, a prospective study which included 250 patients undergoing ureteroscopy for stone treatment, demonstrated that the only intraoperative factor which significantly affected immediate post-operative pain was the duration of use of UAS [ 22 ].…”
Section: Complications Associated With Uas Placementmentioning
confidence: 99%
“…The only operation‐related factor that correlated with severe pain was the total time the UAS was placed: 46.57 (15–110) min with severe pain vs 41.54 (15–140) min in patients without pain. The size of the UAS, operation time, ureteral injury and pre‐ or postoperative stenting were not associated with post‐URS pain . In contrast, in an older prospective study, Kourambas et al found no difference in postoperative pain whether a UAS was used or not.…”
Section: Resultsmentioning
confidence: 91%
“… 32 Prolonged duration of UAS time may be associated with greater post-operative pain. 33 Selection of optimal size and length of UAS is dependent on the user, and often dictated by the compliance of the ureter. Its use is easier in pre-stented ureters and a shorter length (35cm) is generally preferred in females and paediatric patients, while a longer length (45cm) is preferred for male patients.…”
Section: Endourological Armamentariummentioning
confidence: 99%